Galp̀agos - Vonnegut, Kurt. (New York : Delacorta Press, 2006)
A small group of apocalypse survivors stranded on the Galapagos Islands are about to become the progenitors of a brave new human race. Vonnegut is a post-modern Mark Twain. . . . Galapagos is a madcap genealogical adventure.
Keywords: Human evolution -- Fiction; Ghosts -- Fiction; Science fiction, American; Satirical fiction; Islands -- Fiction; Human nature -- Fiction; Galapagos Islands -- Fiction